2013
DOI: 10.1111/odi.12203
|View full text |Cite
|
Sign up to set email alerts
|

COX‐2 gene polymorphisms and risk of chronic periodontitis: a case–control study and meta‐analysis

Abstract: No association was observed in any of the studied COX-2 polymorphisms with CP in North India. But, the study should be replicated in larger sample size to arrive at a definitive conclusion. Meta-analysis suggested a role of rs5275 COX-2 polymorphisms in susceptibility to overall CP, and on ethnic basis, rs20417 showed reduced risk of CP in Chinese population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…There are no significant associations between polymorphisms in COX-2 gene and periodontitis, as showed in Table 1. Nevertheless, contradicting findings are brought by other authors [8] who found an association between COX-2 and periodontitis in women of northern Indian population [36] and in the population of Northwestern European ethnicity [37]. The substitution of C/G at position −765 and substitution of A/G at position −1195, as well as substitution of C/T at position 8473 in the COX-2, were assumed to be polymorphisms associated with periodontitis [38].…”
Section: Resultsmentioning
confidence: 76%
“…There are no significant associations between polymorphisms in COX-2 gene and periodontitis, as showed in Table 1. Nevertheless, contradicting findings are brought by other authors [8] who found an association between COX-2 and periodontitis in women of northern Indian population [36] and in the population of Northwestern European ethnicity [37]. The substitution of C/G at position −765 and substitution of A/G at position −1195, as well as substitution of C/T at position 8473 in the COX-2, were assumed to be polymorphisms associated with periodontitis [38].…”
Section: Resultsmentioning
confidence: 76%
“…Pooled result indicated that a significantly increased risk of the association between the COX2 -765G/C variants and periodontitis in studies with population-based controls and a significantly decreased risk in studies with hospital-based controls was found. Till now, there are only two meta-analyses published on the COX2 -765G/C and periodontitis [ 22 , 23 ], one [ 22 ] paper showed that -765G/C variants could reduce the CP risk in the co-dominant models (GC vs. GG: ORs =0.77, 95% CI = 0.61–0.94) for Asian, while another [ 23 ] paper showed a reduced risk for CP among Chinese population with limited population. Therefore, these two studies were conducted among Chinese populations using smaller number of publications, and did not perform a subgroup analysis by source of controls.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, these two studies were conducted among Chinese populations using smaller number of publications, and did not perform a subgroup analysis by source of controls. Especially for Prakash et al’s meta-analysis [ 23 ], 2 studies performed in Chinese participants were only included, and all the controls were hospital-based. The selection bias would be occurred in hospital-based controls because such populations could not represent the general populations.…”
Section: Discussionmentioning
confidence: 99%
“…For example, COX-2 promoter SNPs and their haplotypes, can influence susceptibility to various cancers, cardiovascular disease, Parkinson's disease, and viral hepatitis C infections [19][20][21][22][23]. Meta-analyses on some of the more commonly explored COX-2 promoter SNPs show that the COX-2 (−765 G > C) polymorphism is associated with the risk of prostate cancer, coronary artery disease, and chronic periodontitis [24][25][26], whereas variation at COX-2 (−1195 A > G) can influence susceptibility to hepatocellular carcinoma and other cancers [27,28]. Meta-analyses of COX-2 haplotypes (−765 G > C and −1195 A > G) also reveal that these haplotypes alter susceptibility to gastric, esophageal, and breast cancers, and Alzheimer's disease [29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%